Peningkatan kinerja operasional perusahaan Jasa Pengurusan Transportasi dalam meningkatkan kepuasan pelanggan - Enjeli Somar; Asep Suparman; Paulus Raga (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2021)
The purpose of this study is to determine the effect of service quality, port facilities, and container stacking places on operational performance in increasing the level of customer satisfaction. The method used in this study is a quantitative method with descriptive type and the data analysis technique uses Path Analysis. The population in this study were 100 respondents consisting of workers in Jasa Pengurusan Transporasi (JPT) companies and JPT customers. The data collection technique uses a questionnaire that has been tested for validity and reliability. Based on the results of the study, it can be revealed that among the quality of service, port facilities, and container storage places, only JPT customer satisfaction with port facilities affect customer satisfaction, both direct and mediated by operational performance.